Multiple Fano Resonances in Plasmonic Metamaterials Composed of Al/Al2O3 Nanomatryushka Structures. Issue 1788 (2015) - Ahmadivand, Arash; Pala, Nezih
ABSTRACT: Metamaterial structures composed of ordered arrays of metallic nanoparticles (NPs) and nanocavities are able to support strong plasmon and Fano resonances in the optical frequencies, where the appeared Fano dips can be utilized in bio/chemical sensing and spectroscopic purposes with a significant sensitivity. Herein, we utilize two concentric compositional Aluminum (Al) nanoshells (Al/Al2 O3 ) to design nanomatryushka (NM) structures in periodic arrays, where each one of Al NPs is covered by a certain thickness of the oxide layer. Depositing studied Al NM arrays on metasurfaces, we determined the optical response of the metamaterial. It is shown that the proposed structure is able to support multiple strong Fano resonances in the visible spectrum. Evaluating the plasmon response of the metamaterial configuration for the presence of various semiconductor metasurfaces (Silicon and GaP), the quality of Fano dips is analyzed for different regimes. In this method, we measured the accuracy and sensitivity of the metamaterial structure by plotting the linear figure of merit (FoM) and quantifying this parameter.